Penurunan Nyeri Persalinan Kala I dengan Aromaterapi Lavender - Nesi Novita; Desy Setiawati; Oktriana Fiesta (Journal of Complementary in Health, 2021)
Maternal pain is a physiological process felt by the mother of labor due to uterine contractions as an attempt to open the cervix and push the baby's head to the pelvis. The dominant pain felt by the maternal mother is the pain when one is active phase. In this phase the pain is felt more severe, sharp and can affect the maternal psychological. One non-pharmacological way to reduce labor pain is with lavender aromatherapy. Aromatherapy is a therapeutic therapy that involves the use of fragrances derived from essential oils. The content of linalyl acetate in lavender can stimulate the release of endorphin hormones that can cause a relaxed, calm and comfortable effect.This study aims to determine the influence of lavender aromatherapy on labor pain in stage I in BPM Palembang City Year 2018. This research type Pre-Experiment with One-Group design model Pretest-Posttest Design. The population in this study were all maternal mothers in BPM Palembang City Year 2018. The sample of the study was taken with Purposive Sampling technique of 30 samples. Result of univariate analysis got pain score before treatment with median 7 (severe pain) and after treatment of pain score with medium 5 (moderate pain). The result of bivariate analysis with Wilxocon Signed Ranks statistic test on the significance level α = 0,05 obtained value ρ value = 0,000 (ρ <0,05) meaning there is a significant difference between pain level before and after given lavender aromatherapy so it can be concluded there is influence of aromatherapy lavender to the first stage of labor pain in BPM Palembang City 2018. It is expected that lavender aromatherapy can be used as a non-pharmacological alternative to reduce labor pain and can be applied in maternity obstetric care.